2020
DOI: 10.1093/pm/pnaa142
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Spinal Cord Stimulation for the Treatment of Axial Low Back Pain: A Systematic Review with Narrative Synthesis

Abstract: Objective Determine the effectiveness of spinal cord stimulation (SCS) for the treatment of axial low back pain (LBP) with or without leg pain. Design Systematic review. Subjects Persons aged ≥18 with axial LBP with or without accompanying leg pain. Intervention Traditional low-frequency, bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The Senza SCS system has already been approved by the FDA in the management of chronic intractable pain of the trunk or limbs associated with failed back surgery syndrome or intractable low back or leg pain. Prior systematic reviews support the use of any SCS in this particular indication; however, they have also found evidence suggesting that 10 kHz SCS devices demonstrate more favorable outcomes relative to traditional devices [ 41 46 ]. More specifically, the reviews by Vallejo et al and Conger et al found similar values for the percentage of patients who experienced ≥ 50% reduction in pain following 10 kHz SCS as estimated in the current meta-analysis on those with upper limb or neck pain (i.e., 83% [95% CI 77–89%]) [ 41 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Senza SCS system has already been approved by the FDA in the management of chronic intractable pain of the trunk or limbs associated with failed back surgery syndrome or intractable low back or leg pain. Prior systematic reviews support the use of any SCS in this particular indication; however, they have also found evidence suggesting that 10 kHz SCS devices demonstrate more favorable outcomes relative to traditional devices [ 41 46 ]. More specifically, the reviews by Vallejo et al and Conger et al found similar values for the percentage of patients who experienced ≥ 50% reduction in pain following 10 kHz SCS as estimated in the current meta-analysis on those with upper limb or neck pain (i.e., 83% [95% CI 77–89%]) [ 41 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior systematic reviews support the use of any SCS in this particular indication; however, they have also found evidence suggesting that 10 kHz SCS devices demonstrate more favorable outcomes relative to traditional devices [ 41 46 ]. More specifically, the reviews by Vallejo et al and Conger et al found similar values for the percentage of patients who experienced ≥ 50% reduction in pain following 10 kHz SCS as estimated in the current meta-analysis on those with upper limb or neck pain (i.e., 83% [95% CI 77–89%]) [ 41 , 46 ]. In terms of pain medication consumption, Pollard et al found that 10 kHz SCS resulted in increased odds of reducing opioid use and greater mean medication dose reduction compared to traditional SCS in patients with intractable spine and limb pain, though there was limited evidence and the results were not statistically significant [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Superior analgesia and functionality scores have been noted with the advent of neuromodulation, including SCS and PNS. [44][45][46] Although systematic reviews of SCS for the treatment of chronic low back pain have been published, 47,48 evidence supporting PNS for the treatment of this condition is currently emerging.…”
Section: Low Back and Trunkmentioning
confidence: 99%
“…It also demonstrated superiority compared to traditional stimulation [7]. More recently, in 2020, a systematic review of 17 independent studies showed low-quality evidence that SCS can be utilized effectively to treat axial LBP [8]. What these studies lack is a specific target in the spinal cord for optimal coverage of axial LBP.…”
Section: Discussionmentioning
confidence: 99%